1993
DOI: 10.1002/mrm.1910290120
|View full text |Cite
|
Sign up to set email alerts
|

A 1H‐NMR method for determining temperature in cell culture perfusion systems

Abstract: This report describes a noninvasive 1H-NMR method for measuring absolute temperatures (+/- 0.2 degrees C) in biological samples and, in particular, in cell culture perfusion systems, utilizing the linear temperature dependence of the water chemical shift relative to the temperature-independent shift of one of the components of the biological medium, e.g., pyruvate, acetate or lactate. The effects of flow on temperature can be monitored and appropriate adjustment of the temperature controller can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 9 publications
4
46
0
Order By: Relevance
“…In vitro studies have demonstrated that this coefficient remains practically independent of tissue type (31) and pH (32). Although a precise relationship between the water proton NMR frequency and temperature for in vivo brain tissue is yet to be established, preliminary data in cell cultures (32) and different biological tissues (31) indicate that this dependence is close to that cited above for pure water. In our experiments, the frequency of the water signal was determined by fitting of the phase of the complex MR signal to a quadratic polynomial:…”
Section: Mr Techniquementioning
confidence: 64%
See 1 more Smart Citation
“…In vitro studies have demonstrated that this coefficient remains practically independent of tissue type (31) and pH (32). Although a precise relationship between the water proton NMR frequency and temperature for in vivo brain tissue is yet to be established, preliminary data in cell cultures (32) and different biological tissues (31) indicate that this dependence is close to that cited above for pure water. In our experiments, the frequency of the water signal was determined by fitting of the phase of the complex MR signal to a quadratic polynomial:…”
Section: Mr Techniquementioning
confidence: 64%
“…The frequency of the MR signal of water depends on temperature and changes with a coefficient of about Ϫ0.01 ppm͞°C (21). In vitro studies have demonstrated that this coefficient remains practically independent of tissue type (31) and pH (32). Although a precise relationship between the water proton NMR frequency and temperature for in vivo brain tissue is yet to be established, preliminary data in cell cultures (32) and different biological tissues (31) indicate that this dependence is close to that cited above for pure water.…”
Section: Mr Techniquementioning
confidence: 99%
“…The index ␣ is the temperature-dependent coefficient of the water chemical shift in units of ppm/°C (or equivalently, ppm/K). It is well known that ␣ for the pure water is about -0.01 ppm/°C (ppm/K) (14) and it is almost independent of tissue compositions (15). Owing to linear and stable temperature sensitivity, the PRF shift method appears to be a reliable method for monitoring temperature change during thermal therapy (12).…”
mentioning
confidence: 99%
“…Several noninvasive thermometers employing NMR techniques have been proposed based on the temperature dependence of NMR parameters, such as relaxation time (30), diffusion coefficient (10), chemical shift (2,6,8,20), or the proton frequency method (11,15,19). Reliability with an error range of less than Ϯ1°C is required for application of these techniques to the estimation of the temperature in the human body under physiological conditions (21,23,32,33).…”
mentioning
confidence: 99%